An Ethics Casebook for Hospitals: Practical Approaches to Everyday Cases - Higgs, H. (Journal of medical ethics, 2001)
In spite of the stress on evidence and audit, clinicians still talk to each other mostly about cases, especially when there are difficulties. So when they come to consider problems in medical ethics, the focus is on case presentation too. However learned the participants, ethical analysis in medicine without cases feels like an egg without salt. Yet the oddity remains that case discussion is often done very badly; new tales are thrown in on a “me too” basis without any apparent questioning about why a second one will help when we haven't got far down the road on sorting out the first. It's not surprising therefore that some still dismiss these discussions as “mere anecdote”, or that there is a continuing critical literature (initiated in part in this journal) about the use and value of the genre itself. This ambivalence must be part of the explanation as …